Hypoxic-ischaemic encephalopathy, perinatal stroke or both? A case report - Adilah W. Ab Rahim; Assyifaa bt Nik Mazian; Halimah Binti Abdul Halim; Azie Jumaatul Adawiyah Nabir; Siti Khadijah Mazli; Aliyyah Mohammad Khuzaini (SAGE Publications, 2025)
Indexed